EL RETO DE LA BRECHA DIGITAL Y LAS PERSONAS MAYORES EN EL MEDIO RURAL ESPAÑOL. EL CASO DE CASTILLA Y LEÓN - Dra. Noelia MORALES ROMO (Fonseca, Journal of Communication, 2023)
This article includes some reflections about the tandem between new technologies, particularly the Internet, and elderly people living in rural areas. This article combines a qualitative (personal interviews and focus groups) and quantitative methodology (analysis of demographic data), aiming to deep about the relationship between relationship between the digital divide and geographical gap for elderly people living in rural areas in Castile and León. Results obtained from this research show the existence of structural elements in these rural areas but also symbolic aspects often overlooked, which must take into account when implementing intervention projects. This study confirms the need to attend to the territory as a variable but also the characteristics of those who have greater difficulties in use and access to ICT, and progress towards equal opportunities.